Israeli Inflation From An International Perspective - Orsmond, David; Fischer, Stanley (Washington, D.C. : International Monetary Fund, 2000)
Israel's post-stabilization experience of moderate inflation and eventual disinflation is compared with experiences in other countries. Lessons that emerge from an examination of international experiences indicate the importance of establishing early on credibility in the nominal anchor and a commitment to persevere with disinflation policies, achieving and maintaining a tight fiscal position, measures to reduce nominal rigidities, and widespread structural reform. Israel falls short on several criteria which explains why taming inflation in the post-stabilization period has been difficult. The paper concludes with a consideration of institutional arrangements that could sustain the current low inflation levels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet